The WIPO academy portfolio of education, training and skills development programs 2024 (WIPO publication ;, 2024)
"This Portfolio serves as a catalogue of all the training opportunities to be offered by the WIPO Academy in 2024 and outlines the content of each course. It gives information to potential participants on eligibility criteria, application formalities, timelines, selection procedures, travel and other relevant necessary information."--